Analyses of reduplicative words in English language - Rakhimova Guzal Yuldashovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses about the analyses of reduplicative words. Also relationship of reduplicative words can be expressed and highlighted with sound representation. The language being studied is characterized by the formation in the middle of reduplicates of clusters.